The Effect Of Operating Costs And Capital Structure On Corporate Income Tax Expense Payable In Mining Sub-Sector Companies Listed On The Indonesia Stock Exchange - Yonson Pane; Deliyanti Simbolon (Outline Journal of Economic Studies, 2025)
This study aims to determine The Effect of Operational Costs and Capital Structure on Corporate Income Tax Expenses Payable to Mining Sub Sector Companies on the Indonesia Stock Exchange in 2015-2019. The research methodology used is quantitative descriptive method. The analytical method used is multiple linear regression with regression equations is Corporate Income Tax Expenses Payable = 171.271,097 + 1.317 Operational Costs - 286,053.394 Capital Struktur + e. The results of the research analysis show that Operational Costs have a significant effect on Corporate Income Tax Expenses in Mining Sector Companies. Based on the results of  partial hypothesis testing, it has a tcount > ttable with a tcount value of 11,249 < ttable  2,03452 and a significant value < 0.05, with a value of 0.000 > 0.05. The results of the research analysis show that the Capital Structure has no effect and is significant on the Corporate Income Tax Expenses in Mining Sub Sector Companies. Based on the results of partial hypothesis testing, it has a tcount < ttable with a tcount value of -2.906 < ttable 2,03452 and a significant value < 0.05 with a value of 0.007 < 0.05. The results of the research analysis show that Operational Costs and Capital Structure have a significant effect on Corporate Income Tax Expenses in Mining Sub Sector Companies based on the results of simultaneous hypothesis testing, namely Fcount > Ftable with a value of 64.274 > 3.29 and a significant value < 0.05, namely by value 0.000 < 0.05.